Kenya - A Micro-Finance Scheme for Women - Kiiru, Washington K.; Pederson, Glenn D. (World Bank, Washington, DC, 2012)
Established in 1981 as an affiliate of Women's World Banking, the Kenya Women Finance Trust (KWFT) aimed to strengthen women's participation in the economic mainstream. It focused on a clientele that had little access to formal lending institutions and sought to strengthen their position by lending to women owners of micro-enterprises and providing the requisite training. Although KWFT started its operations in the early 1980s with several donors providing grants, that support dwindled in the latter part of the decade due to poor performance. By 1990, general mismanagement had resulted in a relatively high number of non-performing loans. Operations had largely ceased and donor confidence was badly eroded. The institution was subsequently restructured with a new board of directors, (comprising professional women), management team and staff. A focused group-based credit methodology was also adopted.